Coastal tourism, market segmentation and contested landscapes. (November 2020) - Pafi, Maria; Flannery, Wesley; Murtagh, Brendan
Abstract: Governments are increasingly adopting Blue Growth strategies as a means of promoting economic development. Although Blue Growth offers development opportunities, from a local perspective it is often concentrated in inaccessible sectors or has negative impacts on coastal communities and landscapes. We argue that to be of use to local communities, tourist experiences of coastal landscapes need to be understood from a community-led, rather than market-led, perspective. Tourist market segmentation can help reveal such experiences but has predominately been used in a narrow, econometric way by the tourism industry, market researchers and policymakers. These approaches often fail to capture the innate experiential nature of coastal tourism and often result in the production of coastal tourism that is unsympathetic to community landscape perspectives and values. To address this gap, this paper adopts an experiential tourist segmentation approach based on community experiences of coastal landscapes. Applied to data collected from a tourist survey on the west coast of Ireland, we identify five landscape experiences: well-being experiences ; conscientious travel experiences ; nature experiences ; coastal change experiences ; and cultural experiences . Based on these experiences, four alternative tourist segments were identified, with significant alignment to communities around sustainable, ethical and locally sensitised forms of tourism, as follows: Blue Health Seekers ; Nature Escapers ; Pristine Seekers ; and Heritage Explorers . The paper concludes by arguing that adopting more experiential and dialogical approaches to market segmentation will identify tourist and communities' perspectives in ways that are compatible and will reveal opportunities for more inclusive and locally accessible forms of Blue Growth.